USAGE OF PHRASAL VERBS AND COMMON PHRASAL - Mamadaliyeva Gulnora Sobirovna (Лучшие интеллектуальные исследования, 2024)
Annotation: Phrasal Verb - A combination of verb and one or more adverbial or prepositional particles, as catch on, take off, bring up, or put up with, functioning as a single semantic unit and often having an idiomatic meaning that could not be predicted from the meanings of the individual parts.